IMPLEMENTASI KONTEN COVID-19 PADA SOAL TIPE PISA: PENGUJIAN SMALL GROUP - Nanda Nabila Al Jannah (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2021)
Mathematics is a science that requires good literacy skills in order to be able to solve problems that exist in everyday life. PISA (Program for International Student Assessment) is one of the efforts to improve mathematical literacy skills aimed at 15 year old students. One of the PISA content that is closely related to everyday life is social content. This study aims to conduct a small group of PISA questions that have been generated in previous studies. The method used is a research and development method. The focus of this research is the small group stage which is tested on two groups of students, each consisting of 3 people, with each student having a different level of thinking ability.